KARAKTER AGRONOMI VARIETAS BAWANG MERAH PADA PERBEDAAN JARAK TANAM DI LAHAN SAWAH - Rajiman Rajiman; Sari Megawati; I Made Pika Adiwijaya; Nurmala Devi Permata (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
The study aimed to determine the adaptability of varieties and spacing of shallots in the rice fields of Sleman Regency to yield. The study used a Factorial Completely Randomized Block Design with 5 replications. The first factor is Variety (V), consisting of V1 = Head, V2 = Crok Kuning, and V3 = Srikayang. The second factor is Planting Distance (J) consisting of J1 = 15 x 15 cm2, J2 = 15 x 20 cm2, J3 = 20 x 20 cm2, and J4 = 25 x 20 cm2. The results showed that the spacing of plants did not significantly interact with all parameters. The use of shallot varieties significantly affected plant height at 3 and 5 WAP, tuber diameter, and stover productivity in wet and dry conditions but had no significant effect on the number of tillers per clump and stover weight per clump in wet and dry conditions. Spacing treatment significantly affected agronomic characteristics, especially weight of stover per clump in wet and dry conditions; stover productivity in wet and dry conditions, but had no significant effect on plant height 3 and 5 WAP, number of tillers per clump, and diameter. The Srikayang variety produced lower productivity than the Crok Kuning and Tajuk varieties. Increasing the width of the spacing will reduce the productivity of shallots.